Análisis psicosocial de los nuevos procesos de institucionalización de los adultos mayores de la parroquia Mena Dos - Bolaños Mangua, Janneth del Rosario (2014)
This research presents a psychosocial analysis of the new processes of institutionalization of older adults in the parish Mena Two, taking as its starting point the participation of the population in the program Sixty Piquito. The research starts from the formation of groups of seniors from the Mena Two sector in the south of the Metropolitan District of Quito, passing through the intervention of the Municipality of Quito with programs designed for seniors and culminates with the analysis of processes institutionalization of elderly in the parish Mena Two on "Sixty Piquito" from a psychosocial approach. Scan from a psychosocial perspective that changes in group attachment relationships and family, occur in older adults from participating in the program Sixty Piquito; and finally determines how the proposed citizen participation Sixty Piquito program has transformed the quality of life of older adults in the case study presented